Beyond Hitler's grasp : the heroic rescue of Bulgaria's Jews - Bar-Zohar, Mikhaʾel, 1938- 1938- (Adams Media Corp, 1998)
Chronicles the actions of "public and private individuals ... who independently risked their lives for the rights of others" and earned Bulgaria the distinction of being "the only Axis-aligned country not to deport its Jews." Despite the formation of a pro-Nazi government and their own version of the Nuremberg laws, "not one Bulgarian Jew ever left the country."--Jacket.